Addressing Equity in Online Education: A Meta-Analysis of Interventions and Outcomes - Guntur Arie Wibowo; Aulia Rahman; Madhan Anis (Penelitian dan Pengembangan Ilmu, 2024)
Equity in online education is a significant challenge amidst the increasing adoption of educational technology, especially for students from various social, economic and cultural backgrounds. This research aims to evaluate the effectiveness of AI-based technologies and adaptive learning in improving equity in online education through a meta-analysis of various interventions and reported outcomes. The method used involved a systematic search of high-quality articles from international databases such as Scopus and Web of Science. The research results show that the integration of this technology can improve educational equality, especially in terms of accessibility, personalization, and inclusivity, although there are differences in results based on student background. The implications of these findings emphasize the importance of developing educational policies and practices that support inclusive and equitable use of technology.